Needs Analysis for the Development of Intelligent Wheelchair Assistant Technology to be Integrated into Hybrid Classes for Students with Disabilities - Eko Risdianto; Helmizar Helmizar; Adhadi Kurniawan; Nor Nazrina Mohamad Nazry (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
This study aims to analyze students' needs for the development of intelligent wheelchair assistant technology to be integrated into hybrid classes for students with disabilities. This research is motivated by the importance of creating a foundation for developing more inclusive and effective technology in the world of education. The use of intelligent wheelchair assistant technology is expected to improve the learning experience of students with disabilities and enable more equitable and inclusive education. The research is part of quantitative research conducted in March 2024. The population in this study consisted of 124 students from several universities. The instrument used in this study was a needs analysis questionnaire sheet consisting of 19 statements with answer choices following the Likert scale guidelines. The results of the needs questionnaire analysis showed that students needed the development of intelligent wheelchair assistant technology to be integrated into hybrid classes for students with disabilities as evidenced by the results of the needs analysis questionnaire of 81.39% in the strongly agree category.